Per- and polyfluoroalkyl substances: Environmental occurrence, health impacts, and advanced removal technologies - Mustapha Saheed; Mohsen Salma; Usman Abdullahi Rakiya; Abubakar Ladio Hassana; Lukman Asiya Muhammad; Jimoh Oladejo Tijani; Ambali Saka Abdulkareem; Muhammad Muhammad Ndamitso; Kehinde Shola Obayomi; Guillermo Díaz-Sainz; Jianhua Zhang (Colloids and Surfaces C: Environmental Aspects, 2026)

Jarisch-Herxheimer reaction: A clinically neglected phenomenon in neurobrucellosis - Abdulbariu Ogirima Uhuami; Abdulrahman Adamu; Buhari Bawa; Abdurrahman Hassan Jibril; Muhammad Bashir Bello; Nafi’u Lawal; Mustapha Umar Imam (Next Research, 2026)

Phytochemical profiles and therapeutic potentials of Thalictrum species in Africa and Asia: a structured review with evidence quality assessment and strategic framework for drug discovery - Sagir Mustapha; Lukman Mustapha; Suciati Suciati; Kayatri Govindaraju; Irma Wati Ngadimon; Muhammad Luqman Nordin; Mustapha Mohammed; Hamza Lawal; Hasiya Usman Jibrilla; Nabil Abdulkarim; Ahmad Khusairi Azemi (Plant Biosystems, 2026)

Paternal lead exposure induces transgenerational oxidative stress and down-regulation of antioxidant genes in Drosophila melanogaster - Aminu Argungu Umar; Isah Musa Fakai; Mustapha Umar Imam; Abduljalil Muhammad Mode (Environmental Science and Pollution Research, 2026)

Polymeric membrane technologies for wastewater treatment and valorization: Advancing sustainable and circular water systems - Mustapha Saheed; Usman Benedict Shama; Abdullahi Karimatu Lami; Elijah Yanda Shaba; Kehinde Shola Obayomi; Awe Omoniyi Babajide; Jimoh Oladejo Tijani; Ambali Saka Abdulkareem; Muhammad Muhammad Ndamitso (Journal of Environmental Sciences, 2026)

Ganoderma in palm oil cultivation: navigating pathogenic challenges through mechanistic insights and innovative management strategies - Nurshafika Abd Khalid; Mustapha Muhammad Isah; Huszalina Hussin; Adibah Yahya (Environmental Sustainability, 2026)

Parental Iron Deficiency Programs Oxidative Stress and Epigenetic Demethylase Dysregulation (TET and KDM2) in Drosophila melanogaster Offspring - Farida Bashar; Kasimu Ghandi Ibrahim; Abdullahi Yahaya Abbas; Muhammad Bashir Bello; Mustapha Umar Imam; Aliu Abdulhameed Zubair (Biological Trace Element Research, 2026)

Transgenerational effects of maternal lead exposure on oxidative stress and antioxidant defense mechanisms in Drosophila melanogaster - Abduljalil Muhammad Mode; Isah Musa Fakai; Mustapha Umar Imam; Aminu Argungu Umar (Toxicology and Environmental Health Sciences, 2026)

In-silico evaluation of Azadirachta indica (neem) against DprE1 of Mycobacterium tuberculosis with functional characterisation - Tolulope Sharon Rumide; Abidemi Esther Ojo; Regina Oghenevwede Golagha; Aanuoluwapo Alake; Zainab Ajoke Suleiman; Lilian Oluchi Nwagbara; Oluwagbemisola Victoria Alu; Aisha Eniola Olayiwola; Mustapha Alkasim; Adebola Sunmola; Mayowa Agbi; Abubakar Lawal Shehu; et al. (In Silico Pharmacology, 2026)

Assessing the impact of agricultural greenhouse gas emissions, financial development, and land use on cereal production in Sub-Saharan Africa: an econometric and machine learning approach - Abubakar Sabo Ahmad; Nazir Muhammad Abdullahi; Umar Shehu Umar; Bello Nasiru Abdullahi; Abdulaziz Nuhu Jibril; Amina Barau Inuwa; Mustapha Muhammad (Environment, Development and Sustainability, 2026)

Deep learning-based detection and statistical analysis of equatorial spread F using ionogram data in the African sector - Yushau Muhammad Sulaiman; Daniel Okoh; Benjamin Wisdom Joshua; Mustapha Abbas (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Mechanistic elucidation of aflatoxin B1 degradation in corn and peanuts via nonthermal plasma: Reactive species and kinetic insights - Mustapha Muhammad Nasiru; Evans Frimpong Boateng; Fawze Alnadari; Sanusi Shamsudeen Nassarawa; Abdullateef Taiye Mustapha; Abdulaziz Nuhu Jibril; Jin Feng; Jiangfeng Song; Jin Wang; Wenjing Yan; Jianhao Zhang; Chunyang Li (Food Control, 2026)

Vacuum steam pulsed blanching enhances enzyme inactivation and quality attributes of Yam via moderate structural modification - Jamilu Mustapha Ahmed; Samir Mowafy; Jiale Guo; Muhammad Hilal Kabir; Samuel Ariyo Okaiyeto; Yanhong Liu (Innovative Food Science & Emerging Technologies, 2026)

Health benefits of plant-based nutraceuticals: An updated review - Ahmadullah Zahir; Mustapha Muhammad Nasiru; Sammra Maqsood; Md Azizul Hakim Shiam (Food and Humanity, 2026)

A review of yellowfin tuna ecology in a changing ocean: Synthesis of habitat dynamics, oceanographic influences, and climate impacts (1963–2023) - Siti Khadijah Srioktoviana; Mukti Zainuddin; Rachmat Hidayat; Alfira Yuniar; Aisjah Farhum; Safruddin; Muzzneena Ahmad Mustapha; Andi Risda Fitrianti Abudarda; Muhammad Ridwan (Regional Studies in Marine Science, 2026)

Tin rich and barren tourmalines of Achemmach (El Hammam district, central Morocco): Mineralogy and physico-chemical characteristics of fluid phases - Azizi Moussaid; Hafid Mezougane; Ilyasse Loudaoued; Mohmed Aissa; Abdelali Kharis; Panagiotis Voudouris; Mohamed Aissa; Mustapha Souhassou; Muhammad Souiri; Abderrahim Ardouz; Hafid Ouahmad (Journal of African Earth Sciences, 2026)

Recent advances in vaccination strategies against acute hepatopancreatic necrosis disease (AHPND) in shrimp for sustainable aquaculture industry: A comprehensive review - Tijani Isa; Riyanto Teguh Widodo; Suzita Mohd Noor; Nur Asyura Nor Amdan; Zulhisyam Abdul Kari; Norhidayah Mohd Taufek; Fathiah Mohamed Zuki; Alias Abdullah; Subha Bhassu; Zarif Mohamed Sofian; Sagir Mustapha; Didi Erwandi Mohamad Haron; et al. (Fish & Shellfish Immunology, 2026)

Evaluation of Thermal Comfort and Adaptive Responses of Secondary School Students in Naturally Ventilated Classrooms in the Tropical Savannah Climate of Nigeria - Tajudeen Dele Mustapha; Ahmad Sanusi Hassan; Muhammad Hafeez Abdul Nasir (Energy and Buildings, 2026)

Vacuum frying of low-fat hairtail: process optimization, physicochemical dynamics, and volatile compounds characterization - Wen Liu; Mustapha Muhammad Nasiru; Jicheng Xu; Chunyang Li (Food Chemistry, 2026)

Ficus benjamina seed extract ameliorates high-sucrose-induced metabolic dysfunction by modulating insulin signalling and antioxidant pathways in drosophila - Muhammad Sani Ismaila; Diane Ignacio; Karla Georges; Kamaldeen Olalekan Sanusi; Mustapha Umar Imam; Kegan Romelle Jones; Venkatesan Sundaram (Next Research, 2026)

Neuroprotective Effects of Ficus deltoidea in Alzheimer’s Disease-Like Rat Model: Insights from Behavior, Histology, and Amyloid Pathology - Abdulhamid Sani Usman; Sushmitaa Dhevii Manoharan; Che Mohd Nasril Che Mohd Nassir; Hafizah Abdul Hamid; Zaw Myo Hein; Anwar Norazit; Jayakumar Murthy; Murizal Zainol; Mohd Amir Kamaruzzaman; Samaila Musa Chiroma; Muzaimi Mustapha; Mohamad Aris Mohd Moklas; et al. (Molecular Neurobiology, 2026)

Innovative photothermal membrane distillation: Mitigating temperature polarisation with rice husk biochar - Chia Ming Liew; Mohd Hafiz Puteh; Mohd Hafiz Dzarfan Othman; Roziana Kamaludin; Siti Maryam Jasman; Parvin Asogan; Rendy Muhamad Iqbal; Mustapha Salisu Muhammad; Huda Nurul; Nor Ain Abu Samah; Jerry Heng; Huda Abdullah; et al. (Journal of Environmental Chemical Engineering, 2025)

Modulatory effects of phytoestrogens, fresh soy milk, and annexin A1 on cell cycle regulation and apoptotic pathways in human leukemic cells and peripheral blood mononuclear cells - Qalidah Mohamad Ali; Ahmad Khusairi Azemi; Siti Hawa Nordin; Sagir Mustapha; Muhammad Luqman Nordin (Biocatalysis and Agricultural Biotechnology, 2025)

Deciphering metabolomics modulations in peanut induced by nonthermal plasma: A quasi-targeted approach - Mustapha Muhammad Nasiru; Evans Frimpong Boateng; Fawze Alnadari; Sanusi Shamsudeen Nassarawa; Anthony Pius Bassey; Jin Feng; Jiangfeng Song; Kabo Masisi; Taing Bunhok; Chuon Mony Roth; Sun Sovath; Hay Pharith; et al. (Food Chemistry, 2025)

Overcoming dormancy, and establishment of a micropropagation protocol to conserve Ziziphus spina-christi - Mustapha Haruna; Muhammad Nakhooda; Shakira Shaik (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Ziziphus spina-christi is a multipurpose wild tree that has been described as endangered in Nigeria and Saudi Arabia due to anthropogenic activities, seed dormancy, and ineffective vegetative propagation methods. The present study aimed to develop efficient seed germination and micropropagation protocols for conservation of Z. spina-christi . The effects of seed pre-treatments and environmental conditions on seed germination were investigated via conventional germination methods. Removal of the seed coat improved germination from 46.6 (control) to 86.6% after 28 days of sowing. Watering the soil every day resulted in significantly lower germination (53.3%) than watering on alternate days (100%) or every four days (86.6%). The optimal temperature for germination was between 21 and 35 °C (86.6%). In the micropropagation experiments, the highest number of shoots/explant (5) was achieved through node culture when the second node was treated with 2 mg L −1 zeatin. Rhizogenesis was only achieved when the basal cut ends of shoots were dipped in 200 mg L −1 indole-3-butyric acid for one hour, resulting in 80% rooting and 4 roots/shoot. Rooted shoots were acclimatised in a sterile potting mix: vermiculite (1:1) with 100% plantlet survival in the greenhouse. Plantlet regeneration via somatic embryogenesis was unsuccessful as embryo induction with 1 mg L −1 each of 2,4-dichlorophenoxyacetic acid, picloram, indole-3-acetic acid, and naphthalene acetic acid inhibited embryo development on maturation media, attributable to the persistence of exogenous auxins in the tissue. This study provides cost-effective methods for conserving Z. spina-christi through seed propagation and also offers the alternate conservation approach of clonal propagation via node culture.

Preparation, characterization, and antibacterial activity of Moringa oleifera‑silver nanoparticles-kaolinite nanocomposite - Mustapha Isah; Nik Ahmad Nizam Nik Malek; Hendra Susanto; Muhammad Hariz Asraf; Abdulrahman Sani Aliero (Applied Clay Science, 2025)

Graphene irradiation heating on corn grains: Effects on bioactive compounds, thermal, structural, and functional properties of corn flour - Abdulaziz Nuhu Jibril; Jiang Zheng; Rui Zhu; Mustapha Muhammad Nasiru; Ambika Paswan; Jichao Huang; Kunjie Chen (Journal of Cereal Science, 2025)

Fabrication and characterization of gelatin/carboxymethyl chitosan composite film incorporated with carvacrol and its preservation efficacy in Chinese mitten crab (Eriocheir sinensis) - Anthony Pius Bassey; Xiaozhen Cui; Isaiah Henry Ibeogu; Fan Wang; Mustapha Muhammad Nasiru; Hadiza Kabir Bako; Linlin Fan; Xiaoli Liu (Food Hydrocolloids, 2025)

Improving Short-term Daily Streamflow Forecasting Using an Autoencoder Based CNN-LSTM Model - Umar Muhammad Mustapha Kumshe; Zakariya Muhammad Abdulhamid; Baba Ahmad Mala; Tasiu Muazu; Abdullahi Uwaisu Muhammad; Ousmane Sangary; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Mosaad Ali Hussein Ali; Aliyu Uthman Bello; Muhammad Muhammad Bala (Water Resources Management, 2024)

Correction to: Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

Neurotoxic snakebites in Africa: Clinical implications, therapeutic strategies, and antivenom efficacy - Abdulbaki Alfa-Ibrahim Adio; Ibrahim Malami; Nafiu Lawal; Amina Yusuf Jega; Bilyaminu Abubakar; Muhammad Bashir Bello; Kasimu Ghandi Ibrahim; Murtala Bello Abubakar; Abdussamad Abdussamad; Mustapha Umar Imam (Toxicon, 2024)

Enhanced streamflow forecasting using attention-based neural network models: a comparative study in MOPEX basins - Abdullahi Uwaisu Muhammad; Tasiu Muazu; Haihua Ying; Abdoul Fatakhou Ba; Sani Tijjani; Jibril Muhammad Adam; Aliyu Uthman Bello; Muhammad Muhammad Bala; Mosaad Ali Hussein Ali; Umar Sani Dabai; Umar Muhammad Mustapha Kumshe; Muhammad Sabo Yahaya (Modeling Earth Systems and Environment, 2024)

From perception to prediction: A comparative study of thermal comfort assessment techniques in school facilities - Tajudeen Dele Mustapha; Ahmad Sanusi Hassan; Muhammad Hafeez Abdul Nasir; Fatemeh Khozaei; Yasser Arab (Energy and Buildings, 2024)

Development of seed germination and in vitro propagation protocols for Vitex doniana - Mustapha Haruna; Muhammad Nakhooda; Shakira Shaik (South African Journal of Botany, 2024)

Development and characterization of edible packaging films based on pork gelatin integrated with serum plasma for pork packaging and preservation - Isaiah Henry Ibeogu; Hadiza Kabir Bako; Fawze Alnadari; Anthony Pius Bassey; Abdulaziz Nuhu Jibril; Tianming Zhou; Mustapha Muhammad Nasiru; Muhammad Shahar Yar; Yunting Xie; Guanghong Zhou; Chunbao Li (Food Bioscience, 2024)

Identification of potential inhibitors of shikimate kinase from Mycobacterium tuberculosis using in silico approach - Mustafa Alhaji Isa; Mohammed Mustapha Mohammed; Muhammad Musa Ibrahim; Falmata Audu Gubio; Fatimah Buba; Somia Shehzadi (Journal of Proteins and Proteomics, 2024)

Dual layer hollow fiber photocatalytic membrane based on TiO2-WO3@GO composite with catalytic memory and enhanced anti-fouling and self-cleaning properties for oilfield-produced water treatment - Ojo Samuel; Asmat Ullah Khan; Roziana Kamaludin; Mohd Hafiz Dzarfan Othman; Tonni Agustiono Kurniawan; Aniqa Imtiaz; Mohammed Faleh Al-Ogaili; Jamilu Usman; Mustapha Salisu Muhammad; Bello Abdulkareem; Obinna Emmanuel Ezenkwa; Mohd Hafiz Puteh; et al. (Chemical Engineering Journal, 2024)

An autoencoder-based stacked LSTM transfer learning model for EC forecasting - Abdullahi Uwaisu Muhammad; Hamza Djigal; Tasiu Muazu; Jibril Muhammad Adam; Abdoul Fatakhou Ba; Umar Sani Dabai; Sani Tijjani; Muhammad Sabo Yahaya; Aliyu Ashiru; Umar Muhammad Mustapha Kumshe; Saddam Aliyu; Faruwa Ajibola Richard (Earth Science Informatics, 2023)

Oilseed meals into foods: an approach for the valorization of oilseed by-products - Gita Addelia Nevara; Shafa’atu Giwa Ibrahim; Sharifah Kharidah Syed Muhammad; Norhasnida Zawawi; Nor Afizah Mustapha; Roselina Karim (Critical Reviews in Food Science and Nutrition, 2023)

Biostratigraphy, organic petrography and carbon isotope chemostratigraphy of the Ordovician-Silurian black shales from the Northwestern Domain of Peninsular Malaysia - Muhammad Aqqid Saparin; Khairul Azlan Mustapha; Mohd Suhaili Ismail (International Journal of Coal Geology, 2023)

Iron deficiency and its epigenetic effects on iron homeostasis - Bashar Farida; Kasimu G. Ibrahim; Bilyaminu Abubakar; Ibrahim Malami; Muhammad B. Bello; Murtala B. Abubakar; Abdullahi Y. Abbas; Mustapha U. Imam (Journal of Trace Elements in Medicine and Biology, 2023)

Petrography and geochemistry of the Moulay Bouazza granitoids (Moroccan Variscan Central Massif). Implications for their origin and geodynamic setting - Ammar Oudy; Hassane Ouazzani; Muhammad Ouabid; Hicham El Messbahi; Mustapha Elabouyi; Afaf Amine; Hind El Haibi (Journal of African Earth Sciences, 2023)

A review of research trends on the usage of photocatalysis for wastewater treatment: bibliometric analysis - Abdussamad Mukhtar Mohammed; Farhana Aziz; Safia Syazana Mohtar; Shakhawan Ahmad Mhamad; Bello Ahmadu; Mustapha Usman Nasir; Khuzaifa Yahuza Muhammad; Madzlan Aziz (Sustainable Water Resources Management, 2023)

A new natural drying method for food packaging and preservation using biopolymer-based dehydration film - Fawze Alnadari; Sam Al-Dalali; Mustapha Muhammad Nasiru; Evans Boateng Frimpong; Yuhang Hu; Dyaaaldin Abdalmegeed; Zhuqing Dai; Abdulrahman AL-Ammari; Guijie Chen; Xiaoxiong Zeng (Food Chemistry, 2023)

Sub-acute toxicity study on hydromethanolic leaves extract of Combretum hypopilinum (Combretaceae) Diels in Wistar rats - Mubarak Hussaini Ahmad; Abdulkadir Umar Zezi; Sherifat Bola Anafi; Omar Yahya Alshargi; Mustapha Mohammed; Sagir Mustapha; Auwal Adam Bala; Surajuddeen Muhammad; Sa’adatu Muhammad Julde; Abubakar Sadiq Wada; Abubakar Ibrahim Jatau (Toxicological Research, 2022)

Efficacy of stem cell secretome in the treatment of traumatic brain injury: A systematic review and meta-analysis of preclinical studies - Suleiman Alhaji Muhammad; Abdullahi Yahya Abbas; Mustapha Umar Imam; Yusuf Saidu; Lawal Suleiman Bilbis (Molecular Neurobiology, 2022)

In silico molecular docking and molecular dynamic simulation of potential inhibitors of 3C-like main proteinase (3CLpro) from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) using selected african medicinal plants - Mustafa Alhaji Isa; Adam Mustapha; Sahar Qazi; Khalid Raza; Ibrahim Alkali Allamin; Muhammad M. Ibrahim; Mohammed M. Mohammed (Advances in Traditional Medicine, 2022)

Substructure design optimization and nonlinear responses control analysis of the mega-sub controlled structural system (MSCSS) under earthquake action - Mustapha Abdulhadi; Zhang Xun’an; Buqiao Fan; Muhammad Moman (Earthquake Engineering and Engineering Vibration, 2021)

Complexing agents for metal removal using ultrafiltration membranes: a review - Mustapha D. Garba; Muhammad Usman; Mohammad A. Jafar Mazumder; Amir Al-Ahmed; Inamuddin (Environmental Chemistry Letters, 2019)

An outbreak of leptospirosis among reserve military recruits, Hulu Perdik, Malaysia - Vasantha Kumari Neela; Nurul Natasya Azhari; Narcisse Joseph; Noraini Philip Mimie; Siti Nur Alia Ramli; Nooreen Farzana Mustapha; Siti Nabilah Ishak; Farah Shafawati Mohd-Taib; Muhammad Afif Yusof; Mohd Nasir Mohd Desa; Garba Bashiru; Zamberi Sekawi (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Erratum to: Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater-A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; S. I. Mustapha; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Effect of resveratrol and environmental enrichment on biomarkers of oxidative stress in young healthy mice - Mustapha Shehu Muhammad; Rabiu Abdussalam Magaji; Aliyu Mohammed; Ahmed-Sherif Isa; Mohammed Garba Magaji (Metabolic Brain Disease, 2017)

Exposure to mobile phone electromagnetic field radiation, ringtone and vibration affects anxiety-like behaviour and oxidative stress biomarkers in albino wistar rats - Abubakar Shehu; Aliyu Mohammed; Rabiu Abdussalam Magaji; Mustapha Shehu Muhammad (Metabolic Brain Disease, 2016)

Isolation and phylogenetic analysis of caprine Orf virus in Malaysia - Ashwaq Ahmed Abdullah; Muhammad Farid Bin Ismail; Krishnan Nair Balakrishnan; Jamilu Abubakar Bala; Homayoun Hani; Yusuf Abba; Mohd Kamaruddin Awang Isa; Faez Firdaus Jesse Abdullah; Siti Suri Arshad; Zeenatul Allaudin Nazariah; Rasedee Abdullah; Noordin Mohamed Mustapha; et al. (VirusDisease, 2015)

Nutrient content of tropical edible seaweeds, Eucheuma cottonii, Caulerpa lentillifera and Sargassum polycystum - Patricia Matanjun; Suhaila Mohamed; Noordin M. Mustapha; Kharidah Muhammad (Journal of Applied Phycology, 2009)

Antioxidant activities and phenolics content of eight species of seaweeds from north Borneo - Patricia Matanjun; Suhaila Mohamed; Noordin Mohamed Mustapha; Kharidah Muhammad; Cheng Hwee Ming (Journal of Applied Phycology, 2008)